PENGARUH PENGGUNAAN MEDIA VIDEO TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Sastramiharja, Ucu Sumardi; Nathanael, Lukas; Permata Sari, Reinada Witri; Kusriani, Fhida (EDUTECH, 2021)
This study was conducted to find out the effect of the use of video media on students' learning motivation. The method used in this study is through a literature study which collects several previous studies to describe the concept of learning media, the concept of video media, the concept of learning motivation, and the influence of media use. video on student learning motivation which includes the theory underlying the use of video media, the use of video media as an effort to increase students 'learning motivation and research results that discuss the effect of using video media on students' learning motivation. Learning through video media can make learning be attractive and increase the motivation and learning outcomes of students. Most research states that the use of video media has a significant influence on the learning motivation of students, especially in adjusting the learning styles of different students. Based on the results of this literature study, it can be concluded that there is an effect of the use of video media on students' learning motivation.Â Studi ini dilakukan untuk mencari tahu pengaruh dari penggunaan media video terhadap motivasi belajar siswa. Metode yang digunakan dalam studi ini adalah melalui studi literatur yang mengumpulkan beberapa penelitian terdahulu untuk mendeskripsikan konsep media pembelajaran, konsep media video, konsep motivasi belajar, serta pengaruh penggunaan media video terhadap motivasi belajar peserta didik yang mencakup teori yang mendasari penggunaan media video, penggunaan media video sebagai upaya meningkatkan motivasi belajar peserta didik serta hasil-hasil penelitian yang membahas pengaruh penggunaan media video terhadap motivasi belajar peserta didik.. Pembelajaran melalui media video dapat membuat pembelajaran menjadi menarik dan meningkatkan motivasi serta hasil belajar peserta didik. Penelitian paling banyak menyebutkan bahwa penggunaan media video memiliki pengaruh yang cukup signifikan terhadap motivasi belajar peserta didik, khususnya dalam menyesuaikan gaya belajar peserta didik yang berbeda-beda. Berdasar hasil studi literatur ini maka dapat disimpulkan bahwa terdapat pengaruh penggunaan media video terhadap motivasi belajar peserta didik.